The contextual interference effect in a serve skill acquisition with experienced volleyball players - Fialho, J. V. A. P.; Benda, R. N.; Ugrinowitsch, H. (Journal of Human Movement Studies, 2006)
The present study investigated the contextual interferenz effect on learning of motor skill using experienced subjects. Experienced Volleyball players (n=10) were allocated to two different groups -random practice and blocked practice - and practiced three Volleyball serves. Through the acquisition phase, during 4 days, both groups participated in one daily Session of practice, with 46 trials each (a total of 184 trials), on serve Volleyball task using two different serves. The transfer test, conducted 10 minutes after the last practice session, consisted of 15 trials of a new serve. The same procedure was followed for the retention test the following day. The data analysis indicated that the random group showed a significantly higher performance in the first block of the retention test. These findings suggested that the contextual interference effect, with different motor programs, can enhance learning in experienced players.